GANGGUAN METABOLISME TRIASILGLISEROL PADA SIROSIS HATI YANG DISERTAI DIABETES MELLITUS - Ischak, Netty (Sainstek, 2007)
Hepatic chrrhosis is a chronic disease characterized by increasing formation of connective tissue that spread from portal spaces and also characterized by nodule formation. One of condition which becoming participating factor of hepatic chrrhosis is diabetes mellitus. Based on a data which is collected from medical record of hospital. In diabetes mellitus, it is most likely happened a disturbance of triacylglycerol metabolim. The increased accumulation of triacylglycerol in liver will be happened due to the imbalance between a formation of tryacylglycerol and a formation of VLDL. Another factor which can cause an abundant accumulation of tryacylglycerol is disturbance of the apoprotein formation, so that a VLDL formation is also disturbed. If that situation happens for a long time, the fatty liver is formed and finally hepatic chirrhosis can be happened.